Tailoring Oxygen Vacancy of Co3O4 Microcubes by Annealing Co3[Co(CN)6]2 Template in Air for Ultrasensitive Humidity Mapping. Issue 2 (6th December 2021) - Yu, Haixia; Guo, Chuanyu; Zhang, Xianfa; Cheng, Xiaoli; Xu, Yingming; Gao, Shan; Huo, Lihua
Abstract : Improving sensitivity under low humidity is highly desirable for the applications of humidity sensors in robotics, intelligent prosthetics, and human–machine interfaces, etc. Herein, by using K3 [Co(CN)6 ] as a single‐source precursor, the Co3 [Co(CN)6 ]2 microcubes were synthesized, which can keep the morphology in temperature range of 380–880 °C as annealed in air. Benefited from the ultrahigh structural stability of the Co3 [Co(CN)6 ]2, the oxygen vacancy in the derived Co3 O4 products can be controllably fabricated through altering calcination temperature. The oxygen vacancy‐abundant Co3 O4 products displayed significantly enhanced response under low humidity (0–6%RH), and thus were applied in scanning a series of water areas to map the humidity distribution. This work presents a promising strategy on rationally designing humidity sensing materials via oxygen defect engineering and provides more possibilities for the application of low‐cost humidity sensors in some emerging fields. Abstract : Fabricating oxygen vacancy on surface of metal oxides is performed as an effective strategy to improve the humidity sensitivity of materials even under low humidity level. This provides more possibilities for the application of low‐cost humidity sensors in some emerging fields in terms of intelligent skin, human–machine interface, contactless screen, etc.